EFFECT OF DESENSITIZATION METHODS DURING THE EARLY MOBILIZATION PHASE IN POST-FRACTURE CONDITIONS OF UPPER EXTREMITY - Shah, Poonam Sunil; Shinde, Sandeep Babasaheb (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: The objectives of the present study were to determine the effect of desensitization methods during early phase of mobilization in post-fracture conditions of upper extremity and to compare the effects of conventional physiotherapy methods and desensitization methods. Methods: A total of 30 subjects having fractures of upper extremity were assigned into two groups. Subjects included in Group A received conventional treatment (hot moist fomentation, mobilization, free exercises, resisted exercises, and strength training exercises). Group B received desensitization methods. The pre- and post-assessment is taken using visual analog scale, range of motion (ROM), manual muscle testing, and disabilities of the arm, shoulder and hand. Result: Desensitization showed significant improvement in ROM for elbow flexion (p=0.0427) (t=2.124) and in strength for shoulder flexion (p=0.0246) (t=2.376), shoulder extension (p=0.0246) (t=2.376), shoulder abduction (p=0.0246) (t=2.376)), shoulder adduction (p=0.0246) (t=2.376), and elbow extension (p=0.0472) (t=2.075) when compared to the conventional treatment, but the conventional treatment showed overall improvement in all outcome variables. Conclusion: Desensitization methods showed a significant effect on reducing pain and improving functional outcome.